Exploring the Evolution and Future Directions of ESG Reporting Research in Accounting: A Bibliometric Analysis - Muchamad Rizky Fauzi; Irna Maya Sari (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Environmental, Social, and Governance (ESG) reporting has become a strategic tool in modern accounting, driven by regulatory pressure and stakeholder demands for greater corporate transparency, yet the literature remains inconsistent on its relationship with financial performance, creating a need for comprehensive field mapping. This study employs a Systematic Literature Review using Scopus data from 2016 to 2025, combining the PRISMA protocol with VOSviewer bibliometric analysis to examine the intellectual structure of ESG accounting research. Analysis of 101 open-access articles confirms strong post-2020 growth, with financial performance, sustainability reporting, and corporate social responsibility as the field’s dominant conceptual anchors, spanning disciplines from accounting and economics to computer science, reflecting the growing role of AI and blockchain in ESG data validation. The field has evolved from descriptive governance studies toward rigorous empirical assessments of ESG performance and SDG alignment, underpinned by stakeholder, legitimacy, and institutional theories. Key gaps remain in areas such as greenwashing detection, SME reporting, and ownership structure. The findings map the current state of ESG knowledge in accounting, expose theoretical and empirical gaps, and offer directions for future research that integrates sustainability with financial reporting to enhance the credibility and strategic value of ESG disclosure for regulators and practitioners.